2007
DOI: 10.1109/tcomm.2007.902512
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Loss Probability in a Finite Size Partitioned Buffer for Quantitative Assured Service

Abstract: Abstract-This paper proposes an approximate yet accurate approach to calculate the loss probabilities in a finite size partitioned buffer system for the achievement of a quantitative assured service in differentiated services networks. The input is modeled as a fractional Brownian motion (FBM) process including J classes of traffic with different packet loss requirements. A first-in firstout buffer partitioned with J −1 thresholds is used to provide J loss priorities. Heuristic expressions of the loss probabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The comparison results among various FBM generation methods, that is, the conditionalised random midpoint displacement algorithm ( RMD 3,3 ) and the fast Fourier transform, and the method based on aggregating a large number of ON–OFF sources with infinite‐variance sojourn times showed that the RMD 3,3 algorithm outperformed the other two because of its relatively lower computational complexity and trace quality . Indeed, RMD 3,3 algorithm is widely used to generate FBM‐based sequences for comparison between simulation and analytical results relative to self‐similar and long‐range dependent Internet traffic . Therefore, in this paper, we generate the FBM‐based self‐similar traffic sequences through RMD 3,3 .…”
Section: Model Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison results among various FBM generation methods, that is, the conditionalised random midpoint displacement algorithm ( RMD 3,3 ) and the fast Fourier transform, and the method based on aggregating a large number of ON–OFF sources with infinite‐variance sojourn times showed that the RMD 3,3 algorithm outperformed the other two because of its relatively lower computational complexity and trace quality . Indeed, RMD 3,3 algorithm is widely used to generate FBM‐based sequences for comparison between simulation and analytical results relative to self‐similar and long‐range dependent Internet traffic . Therefore, in this paper, we generate the FBM‐based self‐similar traffic sequences through RMD 3,3 .…”
Section: Model Validationmentioning
confidence: 99%
“…Internet traffic especially real‐time traffic is self‐similar and long‐range dependent . Studies have shown that the properties of self‐similar traffic have significant effects on QoS provisioning. Therefore, an analytical performance model with this type of traffic is necessary for the previous three QoS schemes.…”
Section: Introductionmentioning
confidence: 99%
“…It was proven in [18] that for a queuing system subject to multiple LRD traffic flows and constant service capacity, the actual service rate received by individual traffic flows can be reasonably modelled as an LRD fBm process. Further, in [31] it was demonstrated that both LRD and SRD processes can be well substituted by a properly parameterized Gaussian process.…”
Section: B Variable Service Capacitymentioning
confidence: 99%
“…Here, is non-negative constant and is often chosen to be 0 as this allows to compute efficiently. Particularly, for a Gaussian traffic flow with mean arrival rate and variance 2 , can be calculated as follows [31], [34]:…”
Section: Tail Distributions Of Packet Delay and Lossmentioning
confidence: 99%
“…An appropriate mathematical framework for the analysis of such systems is generally based on either M/G/1 type system with service time exhibiting the power law or the stochastic differential equation (SDE) driven by the fractional Brownian motion (fBM) [3]. Modeling input traffic by fBM, Cheng, Zhuang and Wang [4] have calculated the loss probability in finite-size partitioned buffer. Using the network traffic studies to model aggregate traffic by a stationary Gaussian process [5], [6], Kim An alternative approach is based on the use of Jaynes' maximum entropy principle [7] subject to partial information available in the form of specified moments.…”
Section: Introductionmentioning
confidence: 99%